Impact of iron biofortified beans on yields and farmers' incomes: The case of Rwanda - Funes, José; Sun, Laixiang; Benson, Todd; Sedano, Fernando; Baiocchi, Giovanni; Birol, Ekin (Agricultural and Applied Economics Association, 2019)
This paper investigates the economic impact of the adoption of conventionally-bred improved iron biofortified beans (IBB) by smallholder farmers in Rwanda. Created through conventional breeding, these beans contain higher levels of dietary iron as compared to beans more commonly used by smallholder farmers in Rwanda. Using observational studies and spatial econometrics methods, we estimated the treatment effect and heterogeneous impact of IBB production on farmers’ yields and potential incomes. We also used a national representative cross-sectional bean farmer survey collected in season B of 2015. Our results indicate that adoption of IBB has contributed to yield and income gains. IBB bush growers, on average, increased their yields by 23% per hectare equivalent to 152 kg (P < 0.05) due to their adoption of IBB, and their potential income by 24% per hectare, that is about $75 (P < 0.04). Farmers that grew IBB climbing varieties, on average, increased their yields by 22% per hectare equivalent to 194 kg (P < 0.04), and their potential agricultural income by 25% per hectare, equal to $116 (P < 0.04). Nationwide, this represents an additional total production value of $2.5 million for all IBB production in season B 2015. Additionally, we found evidence of negative selection by assessing the impact of IBB adoption on those smallholder farmers who are less likely to adopt—for instance, because of access to resources. Evidence suggests this is typically found among farmers that have small land-labor ratios and are closer to markets. Indeed, our findings suggest substantial gains in yields and incomes resulting from this group of farmers adopting iron biofortified seeds. Therefore, based on these results, policies that support greater access to improved iron biofortified bean seeds should be prioritized in Rwanda, and elsewhere in Africa We expect the adoption of IBB to not only improve yields and incomes, but also the dietary iron intake of household members. This would help to reduce the consequences of iron deficiencies—though these effects are measured elsewhere.